Estimate the severity of acute ischemic stroke by optic nerve sheath ultrasound - Esmaeili, Sara; Vahedifard, Farzan; Ebrahimi, Fatemeh; Nazarian, Hossein; Shahidi, Arian; Mirzaasgari, Zahra; Maghsoudi, Mohammadreza (The Ultrasound Journal, 2025)
Background: Timely diagnosis of acute ischemic stroke can aid optimal treatment. Optic nerve sheath diameter (ONSD) can determine increased intracranial pressure (ICP) in such cases. The purpose of this study is to determine the value of ONSD in estimating the severity of acute ischemic stroke.Methods: Patients with acute ischemic stroke who were referred to a stroke center were studied. The ONSD of both the right and left sides was measured by ultrasound on the day of admission. Ischemic stroke severity was determined based on the NIHSS.Results: A strong correlation was found between increased right and left ONSDs and severity of ischemic stroke determined by the initial NIHSS score. Based on ROC curve (receiver operating characteristic curve) analysis, both cut points of 5.65 mm for right ONSD (with 100% sensitivity of and 86% specificity) and 5.75 mm for left ONSD (with a 100% Sensitivity and 88% specificity) were able to predict severe stroke. The value of the right ONSD (Area Under the Curve = 0.959) and the left ONSD (Area Under the Curve = 0.942) indicated a strong predictive value.Conclusions: Ultrasound as a feasible and non-invasive modality might play a role in determining the severity of an acute ischemic stroke, and could be considered a promising first-line decision making tool.